Impact of laryngeal sequelae on voice-and swallowing-related outcomes in paracoccidioidomycosis - Carvalho Alves Pissurno, Neisa Santos; Esteves, Lucas da Motta; Benedito, Juliana Marques; Giglio, Vanessa Ponsano; Carvalho, Lidia Raquel de [UNESP]; Mendes, Rinaldo Poncio [UNESP]; Miranda Paniago, Anamaria Mello (Cevap-sao Paulo State Univ-unesp, 2020)
Background: The present study was carried out aiming to evaluate the impact of laryngeal sequelae on the quality of life of treated paracoccidioidomycosis (PCM) patients. Methods: This cross-sectional study was conducted at the Otorhinolaryngology Outpatient Clinic of the University Hospital, Federal University of Mato Grosso do Sul, Brazil. Thirty-two PCM patients considered clinically and immunologically cured were included: 16 with laryngeal involvement during the active phase of the disease (laryngeal PCM group) and 16 without laryngeal involvement (control group). They were submitted to structured interview, otorhinolaryngology examination, videolaryngoscopy, videoendoscopic swallowing study, completed two questionnaires for voice self-assessment - Voice-related Quality of Life (V-RQOL) and Voice Handicap Index (VHI) - and were asked to score their voices on a scale from zero to 10 (self-assessment of vocal quality). Results: Dysphonia was present in 50% of the cases. Patients with laryngeal PCM presented worse voice-related quality of life scores on the V-RQOL and poorer vocal quality self-assessment than the control group. No significant differences in the VHI were found between the groups. None of the participants developed dysphagic sequelae, although some minor changes were observed on videoendoscopic examination. Conclusion: There were no dysphagia complaints and only a few mild changes were found on the fiberoptic endoscopic evaluation of swallowing, suggesting that this evaluation should be performed only in specific cases. Patients with laryngeal involvement presented worse V-RQOL and self-assessment voice quality. This study contributes to the current knowledge of the functional assessment of the larynx affected by PCM and the impact of dysphonia on quality of life.
Keywords: Paracoccidioidomycosis; Voice; Larynx; Quality of life; Deglutition